Orchiepididymitis as a rare complication of TURP performed four weeks after high-dose-rate brachytherapy for prostate cancer - Rembak-Szynkiewicz, Justyna; Mazgaj, Patrycja; Szopiński, Tomasz; Badziński, Arkadiusz; Hebda, Anna; Wojcieszek, Piotr (Journal of Contemporary Brachytherapy, 2025)
The aim of this paper was to present a rare complication of orchiepididymitis in a patient treated with brachytherapy (BT) for prostate cancer, who underwent trans-ureteral resection of the prostate (TURP) four weeks after BT. A 73-year-old patient with prostate cancer (intermediate-risk group) was eligible for high-dose-rate (HDR) BT combined with androgen deprivation therapy (ADT) for 6 months (leuprorelin). Due to increased symptoms, such as urinary retention after BT, the patient required catheterization. Additionally, bacterial inflammation in the lower urinary tract and prostate was present. Due to prolonged micturition disorders, TURP was performed, leading to chronic orchiepididymitis four months after completion of BT and three months after catheter removal following TURP. Due to long-term inflammation, which was resistant to treatment, the left testicle with left epididymis was removed. Unfortunately, inflammatory symptoms occurred post-operatively in the bed and the left groin. Since these symptoms of varying severity continued, anti-inflammatory drugs and analgesics were introduced. TURP performed too quickly after HDR-BT might cause severe complications. Extreme caution regarding TURP should be exercised in patients undergoing BT. Conservative and pharmacological treatment must be introduced in the occurrence of urinary disorders after BT, and any intervention (TURP) should be performed at least 3-6 months after BT. This is especially crucial because of the development of radiation effect over time.